Respuesta :

axbvw
the average rate of change formula is A(x)= f(x) - f(a)
                                                                           x - a 

Answer:

-2


Step-by-step explanation:

The average rate of change would be change in y divided by change in x

Value of the function at x = 4 is 12

Value of the function at x = 8 is 4

Hence,

  • change in y is [tex]4-12=-8[/tex]
  • change in x is [tex]8-4=4[/tex]

Average rate of change from x = 4 to x = 8 is [tex]\frac{-8}{4}=-2[/tex]

ACCESS MORE